Lungenbildgebung in der Niederfeld-Magnetresonanztomographie - Hinsen, Maximilian; Heiß, Rafael; Nagel, Armin Michael; Levy, Simon; Uder, Michael; Bickelhaupt, Sebastian; May, Matthias (Zeitschrift für Pneumologie, 2024)
Background: Lung magnetic resonance imaging (MRI) examinations are challenging and have not become established in the routine clinical setting. Recent developments in low-field MRI, combined with computer-assisted algorithms for acquisition and evaluation, promise new perspectives for imaging of pulmonary diseases. Objectives: This review aims to inform about the physical advantages of low-field MRI for imaging the lungs, provide a review of the sparse literature, and present first results from a new low-field MRI scanner. Materials and methods: This article provides information on the physical principles, an review of the literature, and our first experiences in lung imaging on a modern 0.55 T MRI. Conclusion: Low-field MRI (< 1 T) may have technical and economic advantages over higher field strength MRI in lung imaging. The physical preconditions of low-field MRI are advantageous for imaging the lungs due to reduced susceptibility effects, increased transversal relaxation times, and lower specific absorption rates. The lower investment and operating costs may enable increased availability and sustainability. Combining modern sequences and computer-based image processing may expand beyond morphological imaging by providing spatially and temporally resolved functional examinations of the lung parenchyma without ionizing radiation. In critical scenarios, like screening and short-term follow-up examinations, and patients at risk, low-field MRI may bridge the gap. These indications may include acute and chronic pulmonary diseases in pediatric patients and suspected pulmonary embolisms in pregnant women.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Field strength; Functional analysis; Image quality; Low-field system; Lung imaging